2015
DOI: 10.1016/j.geotexmem.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A simplified method for predicting the settlement of circular footings on multi-layered geocell-reinforced non-cohesive soils

Abstract: (2015) A simplified method for predicting the settlement of circular footings on multi-layered geocell-reinforced non-cohesive soils. Geotextiles and Geomembranes, 43 (4). pp. 332-344. ISSN 02661144Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/34768/1/A%20simplified%20method%20for%20predicting %20the%20settlement%20of%20circular%20footings%20on%20multi-layered%20geocell-reinforced%20non-cohesive%20soils.pdf Copyright and reuse:The Nottingham ePrints service makes this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, after a certain height, local buckling and straining of geocell walls immobilize the increment in flexural and shear rigidity of the geocells; thus, the loads are not effectively transferred through the geocell layer, leading to a deterioration in performance [23][24][25][28][29][30]. Furthermore, the height of geocells beyond the pressure bulb below the foundation can be considered dormant [31]. The optimum depth of geocells is always less than twice the width of the footing, as validated in most of the available studies [17,18,24,27,32,33].…”
Section: Height Of the Geocells (H)mentioning
confidence: 99%
“…However, after a certain height, local buckling and straining of geocell walls immobilize the increment in flexural and shear rigidity of the geocells; thus, the loads are not effectively transferred through the geocell layer, leading to a deterioration in performance [23][24][25][28][29][30]. Furthermore, the height of geocells beyond the pressure bulb below the foundation can be considered dormant [31]. The optimum depth of geocells is always less than twice the width of the footing, as validated in most of the available studies [17,18,24,27,32,33].…”
Section: Height Of the Geocells (H)mentioning
confidence: 99%
“…They discovered that the geocells distribute the underground stress in the lateral direction, thereby reducing the load that is acting on the buried pipes. Tafreshi, et al [25] conducted a plate bearing test by reinforcing a foundation structure and the lower part of the road pavement with several layers of geocells. They [25] discovered that the underground stress was reduced as the number of geocell layers and the elastic modulus of the ground increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tafreshi, et al [25] conducted a plate bearing test by reinforcing a foundation structure and the lower part of the road pavement with several layers of geocells. They [25] discovered that the underground stress was reduced as the number of geocell layers and the elastic modulus of the ground increased. Pancar and AkpJnar [26] studied the ground reinforcement effect using a variety of geosynthetic materials to improve the bearing capacity of the ground under the pavements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is manufactured into various sizes and depths to accommodate different applications. Geocells have been widely used in a variety of infrastructure applications, such as foundations and subbases (Dash, 2012, Yang et al, 2012, Dash and Bora, 2013, Tanyu et al, 2013, Moghaddas Tafreshi, 2015, Oliaei, 2017, slopes (Mehdipour et al, 2013), retaining structures and embankments (Madhavi Latha andRajagopal, 2007, Zhang et al, 2010). All of these studies have shown that using geocells improves the performance of the infrastructure by reinforcing the granular infill materials.…”
Section: Introductionmentioning
confidence: 99%